Solution‐Processed Organic Solar Cells with High Open‐Circuit Voltage of 1.3 V and Low Non‐Radiative Voltage Loss of 0.16 V. Issue 39 (26th August 2020) - An, Ning; Cai, Yunhao; Wu, Hongbo; Tang, Ailing; Zhang, Kangning; Hao, Xiaotao; Ma, Zaifei; Guo, Qiang; Ryu, Hwa Sook; Woo, Han Young; Sun, Yanming; Zhou, Erjun
Abstract: Compared with inorganic or perovskite solar cells, the relatively large non‐radiative recombination voltage losses (Δ V non‐rad ) in organic solar cells (OSCs) limit the improvement of the open‐circuit voltage ( V oc ). Herein, OSCs are fabricated by adopting two pairs of D–π–A polymers (PBT1‐C/PBT1‐C‐2Cl and PBDB‐T/PBDB‐T‐2Cl) as electron donors and a wide‐bandgap molecule BTA3 as the electron acceptor. In these blends, a charge‐transfer state energy ( E CT ) as high as 1.70–1.76 eV is achieved, leading to small energetic differences between the singlet excited states and charge‐transfer states (Δ E CT ≈ 0.1 eV). In addition, after introducing chlorine atoms into the π‐bridge or the side chain of benzodithiophene (BDT) unit, electroluminescence external quantum efficiencies as high as 1.9 × 10 −3 and 1.0 × 10 −3 are realized in OSCs based on PBTI‐C‐2Cl and PBDB‐T‐2Cl, respectively. Their corresponding Δ V non‐rad are 0.16 and 0.17 V, which are lower than those of OSCs based on the analog polymers without a chlorine atom (0.21 and 0.24 V for PBT1‐C and PBDB‐T, respectively), resulting in high V oc of 1.3 V. The Δ V non‐rad of 0.16 V and V oc of 1.3 V achieved in PBT1‐C‐2Cl:BTA3 OSCs are thought to represent the best values for solution‐processed OSCs reported in the literature so far. Abstract : The relatively large non‐radiative recombination voltage loss (Δ V non‐rad ) is the main challenge for the development of organic solar cells (OSCs). Δ V non‐rad of OSCs can be effectively reduced to 0.16 V by adopting material combinations that deliver high E CT (the energy of charge‐transfer state) and low Δ E CT (energetic difference between singlet excited state and CT state), together with chlorination in donors.